2006
DOI: 10.1116/1.2362758
|View full text |Cite
|
Sign up to set email alerts
|

In As ∕ Al Sb high-electron-mobility transistors by molecular-beam epitaxy for low-power applications

Abstract: In As ∕ Al Sb high-electron-mobility transistor technology has transitioned from research to development stages in recent years. Development efforts at Northrop Grumman Space Technology, in collaboration with the Naval Research Laboratory and the University of California, Los Angeles, have focused on X-band and W-band low-noise amplifier monolithic millimeter-wave integrated circuits fabricated for applications requiring ultralow-power dissipation. The materials for the circuits discussed in this article were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In previous work on InAs-channel HEMTs [with Al(Ga)Sb buffer thicknesses of 2.0 lm to 2.4 lm] we found that rms values of 0.5 nm to 3.5 nm were consistent with high mobilities and MMIC fabrication processes. 22,30 The ability to achieve smooth surfaces after relatively thin buffer layers of Al-rich AlGaSb on GaAs is consistent with our previous scanning tunneling microscopy images of 100-nm layers of AlSb on GaAs. 32 In our current work, we observed no obvious correlation between rms roughness and electron mobility, buffer layer growth rate, or buffer layer thickness over the ranges investigated.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In previous work on InAs-channel HEMTs [with Al(Ga)Sb buffer thicknesses of 2.0 lm to 2.4 lm] we found that rms values of 0.5 nm to 3.5 nm were consistent with high mobilities and MMIC fabrication processes. 22,30 The ability to achieve smooth surfaces after relatively thin buffer layers of Al-rich AlGaSb on GaAs is consistent with our previous scanning tunneling microscopy images of 100-nm layers of AlSb on GaAs. 32 In our current work, we observed no obvious correlation between rms roughness and electron mobility, buffer layer growth rate, or buffer layer thickness over the ranges investigated.…”
Section: Resultssupporting
confidence: 85%
“…It is not always clear why these higher values are sometimes achieved, but careful optimization of the arsenic flux may be important in some cases. 27,30,31 In this work, we did not attempt to optimize the arsenic flux. For growths 1 through 6, the 77-K mobilities ranged from 44,000 cm 2 /V s to 79,000 cm 2 /V s with no obvious correlation with buffer layer thickness or growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…We have also grown structures using a 1.2-nm InAs(Si) doping layer 32,33 as well as InAlSb upper barriers, AlGaSb buffer layers, and small gate-to-channel separations (12 nm). Some samples also included a 20-nm n + InAs cap.…”
Section: Resultsmentioning
confidence: 99%
“…These commonly seen methods for metamorphic device growth usually need the metamorphic buffer layers to be quite thick (around 1 μm) in order to accommodate defects and dislocations resulting from strain relaxation due to lattice mismatch. [17][18][19][20][21] Furthermore, low growth rates are used for the growth of metamorphic buffer layers in order to achieve good material quality. Therefore, growth of such thick metamorphic buffers takes time and greatly raises the production cost.…”
Section: Introductionmentioning
confidence: 99%